FORMULATION AND EVALUATION OF FAST-DISINTEGRATING SUBLINGUAL TABLET OF VALSARTAN FOR THE TREATMENT OF HYPERTENSION - Shukla, Pradeep; Patel, Rakesh; Chokse, Raju (Journal of Biomedical and Pharmaceutical Research, 2018)
Objective: The purpose of the investigation is to formulate fast disintegrating sublingual tablet of Valsartan which is used in the treatment of hypertension to achieve faster onset of action. Materials: Crospovidone(CP), Sodium starch glycolate(SSG), Microcrystalline cellulose(MCC), Magnesium stearate, Mannitol, and Talc. Method: Direct compression method used for the preparation of tablets. The influence of different concentrations of crospovidone and sodium starch glycolate was studied by 5 formulations batches (F1, F2, F3, F4 and F5 ). Here F1-F4 formulations contain different concentrations of superdisintegrants prepared whereas F5 is without superdisintegrants. Result: The hardness of F1 to F5 was ranges from 2.6 kg/cm2 to 3.3 kg/cm². The friability of all the tablets was ranges from 0.83 % to 0.96 %. The wetting time of the tablets were found to be 41 to 81 seconds and disintegration time found to be 43 to 95 seconds. Drug release ranges from 78.70% to 99.47%.Conclusion: F4 formulation (with SSG) showed maximum drug release (99.47%) in half hour and concluded as best formulation. Keywords: Fast disintegrating sublingual tablets, valsartan, solid dispersion